FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA BAGI MAHASISWA AKUNTANSI FEB UNISMA ANGKATAN 2018 (Studi kasus pada Mahasiswa Akuntansi FEB UNISMA angkatan 2018) - Shinta Puspitarini; Dwiyani Sudaryanti; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study was to determine the effect of courage in taking risks, entrepreneurship courses, family environment and campus environment on students' interest in entrepreneurship. The research method used is quantitative research with a Likert 4 scale questionnaire data collection technique for accounting students FEB UNISMA Class 2018. The sample calculation in this study uses the slovin formula with 179 respondents. The data analysis technique used is multiple linear regression with descriptive analysis test, normality test, classical assumption test, coefficient of determination test, partial test and simultaneous test to determine the relationship between variables. The results of the research hypothesis test indicate that courage in taking risks, subjects entrepreneurship, family environment and campus environment simultaneously and significantly influence the interest in entrepreneurship. the influence of courage in taking risks, entrepreneurship courses, family environment has a positive and significant effect, while the campus environment has no effect on interest in entrepreneurship in 2018 FEB UNISMA accounting students.Keywords : Entrepreneurship, Likert, Slovin, Environment